ROTARY IN-VESSEL BIO-CONVERTING OF AGRICULTURE WASES INTO COMPOST - Hasan H. Ali; Hussein M. Flayeh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to convert agricultural waste to organic fertilizer and find the best combinations from agricultural waste, that were used in the research, Composting has always shown to be a reliable and ecologically beneficial technique for removing large amounts of bio-waste. Bio-waste is produced in a variety of sorts (forest residue, farms, agricultural, food industry, and municipal garbage) and is expanding on a daily basis, offering a management and disposal challenge. Millions of tons of cereal vegetable crops, industrial crops, dates and fruits, are produces in Iraq, there are about 20 million tons per year of agriculture waste materials in Iraq, according to estimates, and only a small part of it is used. Composting is an alternate method of material recovery that has no negative consequences. The composting was performed for study with agricultural waste from tree leaves, twigs, date palm, rise husk as a carbon source and manure (sheep, horses, poultry), and vegetable and fruit market waste as a nitrogen source to determine the appropriate mixing, proportion, and combination, as well as the influence of sludge on mixtures. Six distinct experiments were conducted to investigate the alterations in physic-chemical and biological changes during composting utilizing the rotary drum method. Consequently, the compost generated by all experiments had a pH of 6.95–8.00, electrical conductivity of 1.42–2.03 dS.cm⁻¹, a drop in the percentage of overall organic carbon of 16.4–13 percent, a percentage rise in total nitrogen of 0.86–0.19 percent, and a C:N ratio of 8.8–13.7. In this research, the optimal proportions from the various combinations attempted were discovered in drum (B2).